Answers

  • Brainly User
2016-07-10T16:37:21+08:00
Solve for l:

  w          l
---- =  ---------
  l         w + i

w(w+l) = (l) (l)

w² + lw = l²

As quadratic equation in standard form ax² + bx + c = 0 where x is not equal to 0.

l² - wl - w² = 0    where l is not equal to 0

Solve using Quadratic formula:

a = 1     b = -w        c = -w²

Quadratic formula:
           -b +/-  \sqrt{ b^{2}-4ac }  
x   = ---------------------------------             
               2a

Using the Equation above:

     - (-w) +/-  \sqrt{ w^{2}-(4)(1)(- w^{2})  }
l = ----------------------------------------------
                2(1)
      
      w +/-  \sqrt{ w^{2}+4 w^{2}  }
l = ----------------------------------------
                   2
 
      w +/-  \sqrt{ 5w^{2} }
l =  ---------------------------
               2a

       w + w  \sqrt{5}                                              w-w \sqrt{5}
l ₁= --------------------                             l₂ = ----------------------                                                         2                                                           2




0